Economic sustainability of agricultural holdings in Poland in the context of their environmental impact - Wrzaszcz, Wioletta; Zegar, Józef St. (European Journal of Sustainable Development, 2016)
Sustainability of agriculture and agricultural farms is the subject of increasing interests of society and researchers. The main problem of this issue is appropriate methodology of measuring agriculture sustainability, due to its complexity. Different proposals are presented and discussed, and still, there is no generally accepted measures of agriculture sustainability. This problem also concerns agricultural holdings` economic and environment sustainability examination. The particular dilemma is to define modes of agricultural techniques and technologies, that make it possible to combine economic and environmental objectives of agricultural holdings. The purpose of the article is economic sustainability evaluation of agricultural holdings in Poland taking into consideration their potential environmental impact. There were analysed a few groups of farms with potentially different environment impact, namely: a) ecological – organized according with EU legal rules; b) specialized in livestock production; c) not-specialized, with mixed plant and livestock production. Economic sustainability was calculated on the basis of productive and economic indicators, considering subsidies connected with Common Agricultural Policy. The analysis was based on Farm Accountancy Data Network 2004 and 2013. Keywords: farms` sustainability, economic sustainability, agriculture environmental impact, Farm Accountancy Data Network, Poland